2018
DOI: 10.1111/1346-8138.14656
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical features of hidradenitis suppurativa in Korea

Abstract: Hidradenitis suppurativa (HS) is a chronic, relapsing, inflammatory skin disorder. Although several epidemiological studies have been conducted in Western countries, such data regarding Asian populations are scarce. In this study, we sought to investigate the demographic and clinical features of HS in Korea. A total of 438 patients, diagnosed with HS from May 2007 to April 2017, were enrolled and the electronic medical record of each patient was reviewed. Male patients were predominant with a male : female rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
47
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 18 publications
11
47
2
2
Order By: Relevance
“…In European and North American populations, HS has a clear female preponderance, with a female-to-male ratio of approximately 3 : 1Á 8,10,15 The reverse was found in South Korea, with a female-to-male ratio of approximately 1 : 2Á 11,16 Prevalence is highest in the fourth and fifth decades of life. 8,10,15 Onset of HS typically occurs in young adulthood, with a new diagnosis being most common in people aged 18-29 years of age in the USA.…”
Section: Demographicsmentioning
confidence: 99%
“…In European and North American populations, HS has a clear female preponderance, with a female-to-male ratio of approximately 3 : 1Á 8,10,15 The reverse was found in South Korea, with a female-to-male ratio of approximately 1 : 2Á 11,16 Prevalence is highest in the fourth and fifth decades of life. 8,10,15 Onset of HS typically occurs in young adulthood, with a new diagnosis being most common in people aged 18-29 years of age in the USA.…”
Section: Demographicsmentioning
confidence: 99%
“…However, it should be noted that, as mentioned above, most data on prevalence were obtained from the analysis of secondary data and, therefore, possible genderspecific differences, such as willingness to present oneself to a doctor, were not taken into account. Interestingly, a few smaller studies from the Asian region also showed an increased prevalence of HS in men [10,12,25].…”
Section: Discussionmentioning
confidence: 99%
“…HS is thought to be less prevalent in Asian populations, with a paucity of data from this region. However, the number of studies on HS in Asian populations is increasing, with four published articles in year 2018. In particular, these studies originate from East/Southeast Asia.…”
Section: Summary Of Demographic Studies In East/southeast Asiamentioning
confidence: 99%